Islamic cross currency swap : a case study of Bank Islam Malaysia Berhad and Maybank Islamic Berhad - Farhanah binti Mohd Mokhtar (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2015)
Islamic Cross Currency Swap (ICCS) is an Islamic financial hedging instrument that is intended to protect cross-border investments from foreign exchange rate and profit rate exposures. Despite its potential as a powerful tool in the Islamic banking industry, current literatures have deemed the instrument as non-compliant to the Shari'ah because of multiple reasons. Without a thorough research on its execution by the Islamic financial institutions (IFIs) in Malaysia, it would seem unfair to conclude as such. Therefore, the aim of this study is to assess the current market practice of ICCS through evaluation on the mechanics of ICCS executed by two IFIs in Malaysia. In accordance with the aim of this study, a case study methodology is adopted and conducted by means of interviewing the Shari'ah and Treasury Department of Bank Islam Malaysia Berhad (BIMB) and Maybank Islamic Berhad (Maybank). The findings have to a great extent resolved the issues and Shari'ah concerns raised by critically evaluating the mechanics of ICCS executed by the IFIs. Some of the issues include the existence of element of riba (interest), gharar (ambiguity) and maysir (gambling) in ICCS transaction, issues related to concept of risk management allowed by the Shari'ah and usage of the instrument for speculation purposes. Moreover, the concerns are also on the usage of wa'd principle that is similar to a contract, validity of commodity murabahah transactions, recognition of muqasah principle and the issue on combination of multiple contracts into one transaction. The findings also include the similarities and differences in the mechanics of ICCS between the IFIs. Finally, the study covers the effort made by the IFIs in resolving the issues as well as to promote the usage of the product as a very valuable tool in cross-border financial transaction. Therefore, further strengthening of the development of the product and getting consensus among majority scholars are crucial to sustain its demand in the financial market.